Cellulose-enabled Hydrovoltaic Energy Generation: from Molecular and Materials Design to Device Integration - Shin, EunAe; Zan, Guangtao; Zhao, Kaiying; Li, Shengyou; Kim, Gwanho; Kwon, Minji; Kim, HoYeon; Shim, Jin Kie; Park, Cheolmin (Nano-Micro Letters, 2026)
Hydrovoltaic energy generation (HEG) offers a sustainable route for converting water–solid interactions into electricity; however, guidance tailored to cellulose-based systems remains fragmented. This review provides a comprehensive overview of cellulose-based HEG across the four principal device classes—moisture, evaporation, osmotic, and droplet-induced electricity generators. Further, the review clarifies the role of the structural hierarchy of cellulose, its surface chemistry, and its hydration behavior in electrohydrodynamic transport and device-level performance. Beyond summarizing the prior work, we present system-level benchmarking through a consolidated performance table. The table explicitly links the material composition and device architecture with power output, robustness, and representative application scenarios such as power sources, self-powered sensors, and environmental monitoring, thereby offering actionable design guidelines. We further systematically discuss the chemical principles underlying cellulose-enabled HEG, including interfacial charge regulation, electric double-layer formation and overlap, and Donnan and ion-exchange effects, establishing a coherent theoretical basis for optimizing the voltage, current density, power density, and long-term stability. This mechanism-guided perspective connects the design of cellulose materials to the functional performances of moisture, evaporation, osmotic, and droplet systems. Additionally, it outlines practical directions for the sustainable sourcing, standardized testing, and scalable fabrication of efficient and environmentally friendly hydrovoltaic technologies. Hightlights: 1 This review systematically categorizes emerging cellulose-enabled hydrovoltaic energy generators into four types based on their working mechanisms and synthesizes their research progress. 2 Molecular and microstructure–property–performance relationships governing hydration and ion transport are elucidated to provide engineering strategies that leverage cellulose’s intrinsic surface molecular chemistry and structural tunability. 3 Emerging applications in user-interactive electronics based on cellulose-enabled hydrovoltaic energy are comprehensively reviewed across power sources and self-powered sensors for biological and environmental activities.